HUBUNGAN SELF-EFFICACY DENGAN KESIAPSIAGAAN MENGHADAPI BANJIR PADA MASYARAKAT DESA DUSUN DALAM KECAMATAN SIULAK KABUPATEN KERINCI - TIURMAIDA SIMANDALAHI (Badan Penelitian dan Pengembangan Provinsi Sumatera Utara, 2022)
The purpose of this research was to determine correlation of self-efficacy and preparedness in facing flood in Dusun Dalam Villages Siulak Subdistric-Kerinci. The research method used was descriptive analytic with cross sectional approach. The research was conducted in Dusun Dalam Village Siulak District Kerinci Regency, for 1 month from August - September 2019, involving 264 family heads. The sample amounted to 69 people, used the random sampling technique. Univariate and bivariate data analysis through the Chi-Square test, and the data were processed computerized. The univariate results showed that 59.4% of the people were not prepared, 63.8% had low sel-efficacy. The bivariate test explains that there was a correlation between self-efficacy and flood disaster preparedness (p-value 0.026 <0.05). The research recommendation proposed is the optimization of socialization and education related to flooding and its integrated handling, involving all community officials, collaborating with the regional disaster team (BPBD Kerinci), and empowering the potential of existing local wisdom so that the community has preparedness in facing flood disasters. Keywords: self-efficacy; preparedness; flood disaster